MODELING THE PROCESS OF EXTRACTING SENSOR DATA FROM THE TERRAIN USING GENERALIZED NETS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The goal of the paper is to present an original Generalized Net model (GN-model) of the process of obtaining sensor data from the terrain, their analysis using artificial intelligence and their presentation in an operational center to support decision-making in crisis management. By using Generalized Nets, the aim is to create a general model of this process in order to achieve a better basis for research and future analyses of the complex relationships between subjects, objects and impacts in crisis management. To verify the presented GN-model, the simulation environment GN IDE was used, and some results from it are shown, related to the activation of transitions and movement between individual tokens in the net.